(untitled) (Jurnal Bina Praja, 2025)
Tourism development in small island regions such as Larea-rea Island holds great potential to contribute to local economic growth. However, limited infrastructure, inconsistent governance, and low community participation have hampered realizing this potential. This study aims to analyze the role of local government in developing tourism on Larea-rea Island, Sinjai Regency. This study used a qualitative descriptive approach and was conducted from January to March 2024 on Larea-rea Island, located in the Sembilan Island sub-district. Data was collected through field observations, in-depth interviews with stakeholders, including the Tourism and Culture Office of Sinjai Regency, village government officials, and local visitors and supplemented by document analysis. The findings indicate that tourism development on Larea-rea Island remains constrained by inadequate supporting facilities, fluctuating visitor numbers, limited environmental management, and low levels of promotion continuity. The local government has attempted to address these issues through infrastructure development, tourism promotion via social media, environmental conservation efforts, and community empowerment through tourism awareness groups (Pokdarwis). The analysis shows that while these initiatives have had a positive impact, they require stronger coordination, integrated planning, and sustainable policy support. This study concludes that the role of local government must evolve beyond infrastructure provision toward strategic governance that fosters inclusive community participation and long-term destination sustainability.